Ownership Structure and Performance of Public Companies Listed in the Indonesian Stock Exchange - Wasef, Raden Mouna; Kusumastuti, Retno (UI Scholars Hub, 2011)
The aim of this study is to find out if the concentration of the biggest shareholder, the control rights and the ratio of cash flow rights-control rights of the controlling shareholders contributed to profitability. This study uses purposive sampling technique in collecting the data and linear panel regression in analysing the panel data. The result of this study shows that the ownership concentration of the biggest shareholders has positive impact to company profitability as big shareholders have bigger incentive and thus better chance to do supervision upon the management. The study also found that the control rights concentration of controlling shareholders have negative effect to profitability since more concentrated power of the controlling shareholders made the shareholders position stronger and may incline them to gain individual profit which in turn will reduce the company’s profit. On the contrary, higher ratio of cash flow rights to-control rights contributed positively to profitability because higher cash flow rights will tend to prevent the controlling shareholders from expropriating the company’s assets.